Transmissão de Colletotrichum gossypii var. cephalosporioides e Corynespora cassiicola associados à sementes de algodão e soja tratadas com produtos químicos - Françoso, Jonas (2017)
Cotton and soybean crops are prominent among the main agricultural crops in Brazil, since they significantly contribute to the development of Brazilian agriculture. However, the productivity of these cultures can be widely affected by biotic and abiotic factors. Among biotic factors, ramulosis, caused by Colletotrichum gossypii var. cephalosporioides, and target spot, caused by Corynespora cassiicola, derived from infected seeds and crop remains, have caused significant losses in productivity. As alternative controlling these pathogens, products comprised of different fungicides have been widely used. The objective in this study was to evaluate the transmission rate of Colletotrichum gossypii var. cephalosporioides and Corynespora cassiicola using infected seeds and seeds treated with different chemical products. Seeds infected by both pathogens were obtained by using the osmotic conditioning technique, as described in literature. For cotton seeds, the time of exposure to the fungal colony was of 36 hours, while for soybean seeds, time of exposure was of 48 hours. The seeds were posteriorly treated with the chemical products, totalizing five treatments. Sanity, germination, seed and seedling vigor, as well as transmission rates of the fungi were evaluated for both pathosystems. The trials were conducted in laboratory and in plant growth chambers at temperatures of 20°C and 27°C. All tested chemical treatments were effective in reducing the effects of the pathogens and the rates of total transmission in up to 60.54% for C. gossypii var. cephalosporioides, and 85.67% for C. cassiicola. None of the pathosystems presented complete eradication of infective inoculum of the pathogens. With the conditions under which this work was performed, no chemical product was capable of avoiding the transmission of Colletotrichum gossypii var. cephalosporioides and Corynespora cassiicola from the infected cotton and soybean seeds.